1985
DOI: 10.1287/opre.33.4.803
|View full text |Cite
|
Sign up to set email alerts
|

Solving 0-1 Integer Programming Problems Arising from Large Scale Planning Models

Abstract: We present methods that are useful in solving some large scale hierarchical planning models involving 0-1 variables. These 0-1 programming problems initially could not be solved with any standard techniques. We employed several approaches to take advantage of the hierarchical structure of variables (ordered by importance) and other structures present in the models. Critical, but not sufficient for success, was a strong linear programming formulation. We describe methods for strengthening the linear programs, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(39 citation statements)
references
References 15 publications
0
39
0
Order By: Relevance
“…A survey of general ideas for preprocessing is given in Savelsbergh (1994). Other references include Guignard and Spielberg (1981), Johnson et al (1981), Dietrich and Escudero (1990) and Hoffman and Padberg (1991).…”
Section: Lifting Using Multiple Constraintsmentioning
confidence: 99%
“…A survey of general ideas for preprocessing is given in Savelsbergh (1994). Other references include Guignard and Spielberg (1981), Johnson et al (1981), Dietrich and Escudero (1990) and Hoffman and Padberg (1991).…”
Section: Lifting Using Multiple Constraintsmentioning
confidence: 99%
“…[8,10,13,14]). Preprocessing attempts to improve the initial formulation by using several automatic techniques such as infeasibility and redundancy detection, variable fixing and constraint reformulation (see [3,8,9,12,14] among many others). It is well known that preprocessing techniques can considerably reduce the time required to solve large-scale integer programming problems.…”
Section: Introductionmentioning
confidence: 99%
“…In 1985, Johnson, Kostreva and Suhl introduced a more advanced procedure that makes use of information from families of pairwise disjoint packings (see [8,9]) and, in 1996, Escudero, Garín and Pérez improved this procedure allowing overlapping among certain pairs of packings (see [5,12]). This is a theoretical paper whose contribution is twofold.…”
Section: Introductionmentioning
confidence: 99%
“…In [18], coping with natural drainage networks, it is showed that fractal and multifractal properties evolve from arbitrary initial conditions by minimizing the local and global rates of energy expenditure in the system. [30] However, in the general case, the branch and bound technique [19,20,21,22] is usually considered. The basic concept underlying this technique is to divide and conquer.…”
mentioning
confidence: 99%